2012
DOI: 10.1080/07055900.2012.734276
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Modelling: A Primer on Applications, Approaches and Challenges

Abstract: This article examines the current practice of streamflow modelling, a field under development for over a century. A sample of the wide range of assessment and planning applications of streamflow models is presented. The diversity in the use of these models is mirrored in the diversity of model complexity, and modelling approaches ranging from empirical to physically based and from lumped to fully distributed are described with examples. Predictions derived from hydrological models are subject to many sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 253 publications
(349 reference statements)
1
42
0
Order By: Relevance
“…In many cases, the complicated interaction in the hydroclimatic system cannot be characterized by linear models. The Artificial Intelligence (AI) (or machine learning, soft computing) models, including Artificial Neural Network (ANN), Fuzzy Logic (FL), Support Vector Regression (SVR) or Support Vector Machine (SVM), Genetic Algorithm (GA) or Genetic Programming (GP), and wavelet transformation, can be used to model complex interactions of hydroclimatic variables for a variety of applications (Bourdin et al, 2012;Fahimi et al, 2016;Nourani et al, 2014;Rhee & Im, 2017;Wang, Chau, et al, 2009;Yaseen et al, 2015). Several AI models, including the ANN (Mishra & Desai, 2006;Mishra et al, 2007;Morid et al, 2007), SVM (Ganguli & Reddy, 2014), and wavelet transformation (Maity et al, 2016;Özger et al, 2011), have been used to model complicated and nonlinear interactions between drought indicators and influencing factors for drought prediction.…”
Section: Artificial Intelligence Modelmentioning
confidence: 99%
“…In many cases, the complicated interaction in the hydroclimatic system cannot be characterized by linear models. The Artificial Intelligence (AI) (or machine learning, soft computing) models, including Artificial Neural Network (ANN), Fuzzy Logic (FL), Support Vector Regression (SVR) or Support Vector Machine (SVM), Genetic Algorithm (GA) or Genetic Programming (GP), and wavelet transformation, can be used to model complex interactions of hydroclimatic variables for a variety of applications (Bourdin et al, 2012;Fahimi et al, 2016;Nourani et al, 2014;Rhee & Im, 2017;Wang, Chau, et al, 2009;Yaseen et al, 2015). Several AI models, including the ANN (Mishra & Desai, 2006;Mishra et al, 2007;Morid et al, 2007), SVM (Ganguli & Reddy, 2014), and wavelet transformation (Maity et al, 2016;Özger et al, 2011), have been used to model complicated and nonlinear interactions between drought indicators and influencing factors for drought prediction.…”
Section: Artificial Intelligence Modelmentioning
confidence: 99%
“…Digital Elevation Models (DEMs) are one of the most important spatial input data sets in hydrological modelling (Bourdin, Fleming, & Stull, 2012;Wu, Li, & Huang, 2008). DEMs constitute a key spatial layer for estimating a watershed's channel networks, slope gradients, flow direction and accumulations, and several other controls of the water movements in landscapes (Moore, Grayson, & Ladson, 1991;Wechsler, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that statistical downscaling was better able to assess climate change effects on spring peak and summer low flows because of improved prediction of precipitation. Bourdin et al (2012) indicated that statistical downscaling approaches have been more popular because of Table 3). Adapted and updated from Bush et al (2014).…”
Section: Runoff and Streamflowmentioning
confidence: 96%
“…A hydrologic model inter-comparison might yield some useful insights, particularly considering the effects of model structural uncertainty which have led to differences in the representation of evaporation and snowmelt processes (Jiménez Cisneros et al 2014). Scenarios should include both climate and land changes (Bourdin et al 2012).…”
Section: Watersheds With Large Lakes And/or Glaciersmentioning
confidence: 99%
See 1 more Smart Citation